Efficacy of a new balloon catheter for internal cardioversion of chronic atrial fibrillation without anaesthesia. Issue 2 (1st February 1998) - Alt, E; Ammer, R; Lehmann, G; Schmitt, C; Pasquantonio, J; Schömig, A
Abstract : Objective: To compare a new internal cardioversion system incorporated into a balloon guided catheter with a conventional two electrode system in patients with atrial fibrillation (AF). Design: Prospective study. Patients: 74 patients with chronic AF treated by internal cardioversion. Materials: A 7.5 F balloon catheter with high energy electrode arrays each consisting of six 0.5 cm platinum rings. Brachial vein access enables one electrode array to be placed in the left pulmonary artery (distal pole) and the other at the lateral right atrial wall (proximal pole). The conventional two electrode system consists of 6 F electrodes placed in the proximal left pulmonary artery (anode) and the lower right atrium. Interventions: Internal cardioversion was performed by shocks delivered in 40 V incremental steps from an external defibrillator. Shocks were applied by the new device to 32 patients (group A) and by the conventional sysytem to 42 patients (group B). Results: The groups differed with respect to system positioning (9.2 (7.3) v 12.3 (8.1) minutes, p < 0.05) and fluoroscopy times (1.7 (1.0) v 3.3 (2.1) minutes, p < 0.01). Sinus rhythm was restored in 30 patients of group A and in 39 of group B (NS) with mean (SD) energy requirements of 8.4 (3.1) J and 7.2 (3.1) J, respectively (NS). Conclusions: This new method of internal cardioversion has comparably high primary success rates and low sedation requirements with single and two lead systems.